2020
DOI: 10.1163/23641177-bja10006
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Language Barriers in Science for Students with Special Educational Needs

Abstract: An increased focus on science instruction and science learning for students with special education needs has been growing over the past decade. Research studies, particularly meta-analyses focused on science for students with disabilities, show investigators are interested in what science strategies and approaches (e.g., graphic organizers, inquiry-based instruction,) work for students regardless of identified need (e.g., learning disabilities). However, researchers have noted that science instruction can ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Readers who have prior knowledge and greater experience with scientific topics can more readily make connections between what they are reading and what they know (Cervetti & Hiebert, 2015; McLaughlin & Overturf, 2012; Pearson et al, 1979). Because argumentation involves recursive thinking between evaluation of data and justification of reasoning, then synthesis of one’s position using discipline-appropriate language and vocabulary (Berland & McNeill, 2010; Kim, Relyea, et al, 2021b), utilizing effective strategies to also shore up and accelerate content knowledge and vocabulary, continues to be essential (S. Boyle et al, 2020; Cervetti et al, 2016; Graham et al, 2020).…”
Section: Purpose Of the Current Studymentioning
confidence: 99%
“…Readers who have prior knowledge and greater experience with scientific topics can more readily make connections between what they are reading and what they know (Cervetti & Hiebert, 2015; McLaughlin & Overturf, 2012; Pearson et al, 1979). Because argumentation involves recursive thinking between evaluation of data and justification of reasoning, then synthesis of one’s position using discipline-appropriate language and vocabulary (Berland & McNeill, 2010; Kim, Relyea, et al, 2021b), utilizing effective strategies to also shore up and accelerate content knowledge and vocabulary, continues to be essential (S. Boyle et al, 2020; Cervetti et al, 2016; Graham et al, 2020).…”
Section: Purpose Of the Current Studymentioning
confidence: 99%
“…This approach is supported by several national science associations and can help make the classroom a place where all students feel valued, respected, and able to fully participate in science class (Trundle, 2008). Additionally, note taking can help keep students alert, focused, and accountable while they listen, and serve as a record of what was said in a lecture or discussion (Boyle, 2010(Boyle, , 2012Boyle et al, 2020). Furthermore, writing in class and reading notes prior to testing improve recollection, which is critical for exam success(Oregon State University, 2021).…”
Section: Recommended Strategies and Practices In Science Classes For ...mentioning
confidence: 99%
“…Another suggested teaching strategy through research studies is Project-based learning (PBL) can help teachers tailor projects, learning routes, and assessment criteria to meet the needs and interests of their students (Kortam et al, 2018). Also, The Universal Design for Learning (UDL) framework is a threeprinciple framework that includes visual representation options, engaging students in learning tasks, and varying how students express what they know (Boyle et al, 2020;CAST., 2018). The right science class setting can inspire students to be more responsible about their learning, such as a creative teacher, appropriate questioning technique, planning regarding learning needs and goals, and motivating students to attend science classes (Lee et al, 2008;Rogers, 2019).…”
Section: Recommended Strategies and Practices In Science Classes For ...mentioning
confidence: 99%
“…Learners have developed their own understanding different from the scientific meaning (Sullenger, 2005). The argument is how can science, literacy and language be linked in the classrooms (Boyle, Rizzo, & Jonte, 2020). In concurrence as early as 1998, Rollnick indicated that the learner's success in learning science is dependent on the knowledge of learning English language.…”
Section: Problem Statementmentioning
confidence: 99%